Is the design a vector to be considered in the agri-food industry? An interprofesional analysis in Andalusia (Spain). - González-Yebra, Óscar; Aguilar, Manuel A.; Aguilar, Fernando J. (Springer Nature, 2019)
We currently live in a globalized world where the imperative need to both generate added value and new products and services has been strengthened. Some of the prob-lems pending to solve can be properly faced from the field of "Design". However, and up to now, there is no design science serving as a knowledge pivot for developing and building the solutions required. On the other hand, design is cross-cuttingly present in the different activities of a country like Spain, where one of the most important sec-tors is agriculture. Starting from this context, a survey about the role of design in the agri-food industry has been developed through the well-known Delphi method, con-stituting a panel of experts from the private sector of Andalusia. To the best of our knowledge, this is the first study in which a forum of these characteristics has aimed to involve both CEOs and managers of agri-food businesses and design professionals to work together around this topic. The results obtained suggest that design compo-nent in the agri-food industry is mainly present in activities related to graphic design, showing less presence in the industrial-product design or, specially, in the environ-ment design. They also point out that design is an important tool to explore in the agri-food sector since it might provide both tangible and intangible benefits. The find-ings of this work seem to be very valuable as a diagnostic to characterize the design component, also contributing to uncover and develop the design as an important fac-tor of dynamization.
https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Industria transformadora de productos agrícolas; Industria alimentaria; Diseño industrial; Diseño gráfico; Design; Agri-food industry; Innovation; Interdisciplinary research; Delphi method; Industrial design training; Design-driven innovation